Diligent mathematician from southeast Lithuania (on the occasion of asociate professor A. Miškelevičius 80th anniversary - Misevičius, Gintautas; Verikaitė, Vitolda (Lietuvos matematikos rinkinys, 2016)
A survey of life and activity of outstanding Lithuanian mathematician and lecturer, asociate professor of the chair of Mathematical analysis of Vilnius University Algirdas Miškelevičius (1936–1990). A. Miškelevičius examined the uniform and averconvergence of integrales of type of Laplase–Styltjes (A), (B) and the series of Dirichlet (1), (C). A. Miškelevičius improved the results of famous mathemacians V. Bernstein, M. Ostrovski, G. Lunc, H. Vasalo, D. Poya, N. Abel, M. Riesz. The exclusive article of A. Miškelevičius has been written in cooperation with a world recognized professor Šlioma Strelitz on the convergence of Laplace-Stilties integral. A. Miškelevičius adressed lot of attention to developement of metodology Mathematical analysis. He wrote textbooks and educational books on Functional analysis. A. Miškelevičius was a great educator, sincere and dutiful member of a team.
Keywords: series of Dirichlet; complex exponent; overconvergence of series and integrals; simpleconnected set